EXPLORING TEACHERS’ PERCEPTION TOWARD THEIR PROFESSIONALISM IN TEACHING ENGLISH - Ety Fahriani; Iskandar Abdul Samad; Saiful Saiful (Universitas Syiah Kuala, 2020)
This study is intended to explore the teachers’ perception toward their professional development in teaching English at senior high schools in Bireuen. This study employs a qualitative design in collecting and analyzing the data.To collect the data, 30 English teachers of 146 English teachers in Kabupaten Bireuen were randomly chosen as the participants. A set of Likert Scale questionnaires was given to 30 teachers and 10 of the teachers were interviewed by using a guided interview to explore the general perception about the teachers’ perception toward their professional development and their effort to improve their professionalism in teaching English. The finding revealed that the English teachers in Kabupaten Bireuen presumed themselves as professionals in doing their occupation. It is due to their perception that they accomplished the four pre-requirement competencies namely pedagogical, social, personal, and professional. They improved pedagogical competence by collecting teaching materials from the internet, books, and their seniors and learning about new teaching methods. They improved their competence by building a good relationship with students, parents, and school stakeholders.The teachers improved their professional competence by joining the forum of subject matter teacher (MGMP), attending education seminars, training, and workshops, and they improved the competence by behaving with good characters.